2018
DOI: 10.1111/nyas.13726
|View full text |Cite
|
Sign up to set email alerts
|

Music‐supported therapy for stroke motor recovery: theoretical and practical considerations

Abstract: Music may confer benefits for well-being and health. What is the state of knowledge and evidence for a role of music in supporting the rehabilitation of movements after stroke? In this brief perspective, I provide background context and information about stroke recovery in general, in order to spark reflection and discussion for how we think music may impact motor recovery, given the current clinical milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Motor deficits of the upper extremity are common in patients with stroke and have a relevant impact on patients’ activities of daily living, independence, and quality of life ( Morris et al, 2013 ). Motor function recovery for this population relies primarily on motor rehabilitation ( Langhorne et al, 2011 ), thus music-based therapies have received ample research attention in the past years (for discussion, see Thaut and McIntosh, 2014 ; Zhang et al, 2016 ; Moumdjian et al, 2017 ; Chen, 2018 ; Altenmüller and James, 2020 ; Grau-Sánchez et al, 2020 ; Huang et al, 2021 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Motor deficits of the upper extremity are common in patients with stroke and have a relevant impact on patients’ activities of daily living, independence, and quality of life ( Morris et al, 2013 ). Motor function recovery for this population relies primarily on motor rehabilitation ( Langhorne et al, 2011 ), thus music-based therapies have received ample research attention in the past years (for discussion, see Thaut and McIntosh, 2014 ; Zhang et al, 2016 ; Moumdjian et al, 2017 ; Chen, 2018 ; Altenmüller and James, 2020 ; Grau-Sánchez et al, 2020 ; Huang et al, 2021 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Positive effects have also been found on communication-related and quality-of-life outcomes (3). Chen provided an overview of three meta-analyses discussing the effectiveness of music interventions after stroke and highlighted a gap in the literature (5)—the author concluded that although music interventions seem to be promising for enhancing clinical motor recovery after stroke, the quality of evidence is still rather low. It was suggested that more phase I and II studies are necessary as underlying mechanisms, and the nature (true motor recovery or compensation) of these improvements is still unclear (5).…”
Section: Introductionmentioning
confidence: 99%
“…Chen provided an overview of three meta-analyses discussing the effectiveness of music interventions after stroke and highlighted a gap in the literature (5)—the author concluded that although music interventions seem to be promising for enhancing clinical motor recovery after stroke, the quality of evidence is still rather low. It was suggested that more phase I and II studies are necessary as underlying mechanisms, and the nature (true motor recovery or compensation) of these improvements is still unclear (5). Indeed, without taking into account the movement quality of a certain task, it is impossible to discriminate between “true recovery” and “compensation” of motor patterns (7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while well-powered Phase III and IV RCTs are the ultimate aim, Phase I and II studies on the mechanisms underlying music-based interventions remain crucial for the design of better interventions. While this need has been discussed previously in the context of stroke recovery (Chen, 2018), the current article generalizes the reviewed literature to neurodegenerative diseases, including Alzheimer's Disease and Parkinson's Disease. From there, a few possible underlying mechanisms are described through which music can target specific brain networks.…”
Section: Music-based Interventions As Complex Interventionsmentioning
confidence: 86%